The notions of co-reference and locality as theoretical resources for the teaching of FN in Spanish - Esquivel Villafana, Jorge (2006)
The notions of co-reference and locality, theoretical constructs elaborated by generative grammar in its version of the theory of Rection and Binding to point out the referential identity between the anaphora and its antecedent, in addition to establishing between them a sort of hierarchy within a local domain relation (sentence or subordinate clause), allow the development of syntactic descriptions with a high level of explanatory adequacy. Such notions, seen as a means of making explicit semantic-syntactic aspects that the speaker intuitively knows about the different types of FN, make it possible to configure concrete structural descriptions that systematize their presentation and objectively favor the intelligibility of the syntax.